Problem-Based Learning (PBL) Model to improve numeracy skills and self-confidence of middle school students - Margaretha Madha Melissa; Erfiana Nur Laila; Marcelia Puspita Ningrum; Odilia Rosa Kusuma (Journal Focus Action of Research Mathematic (Factor M), 2024)
Numeracy is important to develop because it is related to students' ability to solve mathematical problems in everyday life. This research aims to improve students' numeracy and self-confidence through the application of the Problem Based Learning (PBL) learning model. The type of research is classroom action research (CAR) with an adaptation of the Kemmis and Mc Taggart model. The subjects of this research were 30 class VII students at SMP Negeri 1 Depok. The data collection instruments used included a self-confidence questionnaire and numeracy test. Data analysis techniques for self-confidence questionnaires and numeracy test results are averaged, categorized and the gain score value analyzed. The results of this research show that students' numeracy and self-confidence increase after PBL learning. The increase in students' numeracy can be seen from the gain-score of students’ numeracy test from Cycle 1 to Cycle 2. The Problem Based Learning model also increases students' self-confidence based on the increase in categories achieved by students from Cycle 1 to Cycle 2. Therefore, the researcher Others can use the PBL model to increase students' self-confidence and numeracy in other materials.